Analisis Kepemimpinan Kepala Sekolah Dalam Meningkatkan Kinerja Guru Di SMA Negeri 8 Batanghari - Saputra, Al Indra; Masbirorotni, Masbirorotni; Aprillitzavivayarti, Aprillitzavivayarti (Yayasan Rahmat Islamiyah, 2023)
This study aims to describe: 1) Principal's leadership in improving teacher performance at SMA Negeri 8 Batanghari. 2) Factors supporting the principal's leadership in improving teacher performance at SMA Negeri 8 Batanghari. 3). The inhibiting factor of the principal's leadership in improving teacher performance at SMA Negeri 8 Batanghari. This type of research is qualitative research. The nature of this research is descriptive. Data collection techniques with the method of observation, interviews and documentation. Testing the validity of the data by triangulation. While data analysis with data reduction, data presentation, conclusion drawing and verification. From this study it can be concluded that 1) Principal leadership in improving teacher performance refers to a type of transactional leadership, namely the principal supervises, gives awards and also the principal gives sanctions to teachers, 2) Factors supporting the principal's leadership in improving teacher performance, namely: The existence of a good and harmonious relationship between the principal and teachers, the availability of facilities and infrastructure, the presence of competent teachers, and the ability and knowledge of the principal in managing schools, 3) Factors The obstacles to the principal's leadership are that there are still some teachers who are not confident, the time management of teachers is not well organized, there is jealousy among teachers, there is a distance between senior teachers and junior teachers, and the principal is still reluctant to direct orders to the principal teacher.